Factors predicting outcome after selective ERCP in the laparoscopic era. - Robertson, G. S. (Royal College of Surgeons of England, 1995)
This study assessed the outcome of 342 patients with in situ gallbladders undergoing ERCP for suspected choledocholithiasis. The result of ERCP was found to play a significant role (P < 0.0001) in determining whether patients were subsequently managed conservatively (n = 152) or underwent either laparoscopic (n = 110) or open (n = 80) surgery. Those undergoing laparoscopic surgery were noted to be younger (P = 0.0001) and were less likely to be jaundiced (P = 0.0015) or have CBD stones at ERCP (P = 0.0295). In 28 patients with CBD stones remaining after ERCP, pre- rather than postoperative timing of ERCP prevented a potential second operation. The current success rate of 85% in clearing CBD stones at ERCP cannot support a routine policy of intraoperative cholangiography followed by postoperative ERCP.